2021
DOI: 10.48550/arxiv.2109.15237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Turbulent magnetic fields in the merging galaxy cluster MACS J0717.5+3745: polarization analysis

K. Rajpurohit,
M. Hoeft,
D. Wittor
et al.

Abstract: We present wideband (1−6.5 GHz) polarimetric observations, obtained with the Karl G. Jansky Very Large Array (VLA), of the merging galaxy cluster MACS J0717.5+3745, which hosts one of the most complex known radio relic and halo systems. We use both Rotation Measure Synthesis and QU-fitting, and find a reasonable agreement of the results obtained with these methods, in particular, when the Faraday distribution is simple and the depolarization is mild. The relic is highly polarized over its entire length (850 kp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…The depolarisation is affected by the amount of ICM along the line-of-sight, see e.g. the discussion in [13]. When correcting for the Faraday rotation along the line-of-sight one finds the intrinsic polarisation angle of the synchrotron emission.…”
Section: Introductionmentioning
confidence: 99%
“…The depolarisation is affected by the amount of ICM along the line-of-sight, see e.g. the discussion in [13]. When correcting for the Faraday rotation along the line-of-sight one finds the intrinsic polarisation angle of the synchrotron emission.…”
Section: Introductionmentioning
confidence: 99%
“…For several relics the magnetic field which corresponds to polarisation direction (i.e., the so-called polarisation B-vector) is astonishingly well aligned with the relic morphology, i.e., the orientation of the shock surface, most spectacularly for the Sausage relic [11,14]. Other relics which show this alignment are for instance the Toothbrush [9], the northern relic in PSZ1 G096.89 + 24.17 [15] and the relic in MACS J0717.5 + 3745 [13]. The orientation of the polarisation has revealed that the magnetic field is well aligned with the surface of the shock.…”
Section: Introductionmentioning
confidence: 85%
“…Some relics show a strong frequency dependent depolarisation which can be attributed to the Faraday depth dispersion due to the magnetoionic intra-cluster medium (ICM) along the line-of-sight from the observer to the emission region. The depolarisation is affected by the amount of ICM along the line-of-sight, see e.g., the discussion in [13]. When correcting for the Faraday rotation along the line-of-sight one finds the intrinsic polarisation angle of the synchrotron emission.…”
Section: Introductionmentioning
confidence: 99%
“…Galaxy clusters undergoing mergers often show spectacular, megaparsec-scale radio relics and radio halos (see van Weeren et al 2019, for a recent review). The radio spectra of such sources are steep (α ≤ −1.0 where Di Gennaro et al 2021;Rajpurohit et al 2020aRajpurohit et al , 2021a and believed to originate from shock fronts generated in the intracluster medium (ICM) when galaxy clusters merge (Ensslin et al 1998;Roettiger et al 1999). This connection has been established by finding X-ray surface brightness and temperature discontinuities at the location of some relics (see e.g., Sarazin et al 2013;Ogrean et al 2013;Shimwell et al 2015;van Weeren et al 2016;Botteon et al 2016;Thölken et al 2018;Di Gennaro et al 2019).…”
Section: Introductionmentioning
confidence: 99%